A survey on electronic dialogue, risk assessment, customer access, and customers relationship lifetime - Lestari, Puji Tri; Fernando, Yudi; Ikhsan, Ridho Bramulya; Wahyuni-Td, Ika Sari; Prasarry, Yudhita Valen; Mergeresa, Fineke (Institute of Electrical and Electronics Engineers Inc., 2022)
The customer lifetime relationship has challenged the firms to engage with loyal customers. Typically the relationship has no longer electronic compared to the conventional ones. This study aimed to determine the effect of electronic dialogue and risk assessment on customer access and relationship lifetime. The data were collected electronically and analysed using Structural Equation Modeling (SEM) based on component or variance of Partial Least Square (PLS). We found five hypotheses are accepted. The results prove that electronic dialogue affects customer access. Simultaneously, the findings found that electronic dialogue has significant results on lifetime value. At the same time, risk assessment impacts customer access and relationship lifetime value. The findings contribute to the extent of the electronic dialogue framework on consumer-based research. This research implies that the company needs to increase and monitor the relationship lifetime value frequently. The creative strategy needs to be applied to improve electronic dialogue, risk assessment, and customer access.